A possible new ritual scene from the Mycenaean settlement at Kontopigado, Athens - Kardamaki, Eleftheria (Opuscula. Annual of the Swedish Institutes at Athens and Rome, 2025)
The study deals with a pictorial scene partially preserved on a kylix of the 14th century BC (Late Helladic IIIA2) from the Mycenaean settlement of Kontopigado, 5 km south of the Athenian Acropolis. The scene includes part of a beaked jug, a vase that in Minoan and Mycenaean religious realm was connected with libations of liquids. Based on an analysis of the iconography of libation jugs, the study tentatively proposes that the scene presents a ritual involving water libations and possibly a rare depiction of a showery cloud, allowing new insights into religious iconography of the 14th century BC.